Endovascular versus open repair of ruptured abdominal aortic aneurysm. Issue 5 (October 2016) - McHugh, S.M.; Aherne, T.; Goetz, T.; Byrne, J.; Boyle, E.; Allen, M.; Leahy, A.; Moneley, D.; Naughton, P.
Abstract: Introduction: Endovascular aneurysm repair (EVAR) is a comparatively less invasive technique than open repair (OR). Debate remains with regard to the benefit of EVAR for patients with ruptured abdominal aortic aneurysm (RAAA). We sought to evaluate and report outcomes of EVAR for RAAA in an Irish tertiary vascular referral centre. Methods: Patients undergoing emergency surgery for ruptured or symptomatic AAA were identified from theatre logbooks and HIPE database. Retrospective chart review was undertaken. Data were exported to IBM SPSS version 21 for statistical analysis with p < 0.05 considered significant. Results: A total of 41 patients underwent surgery for RAAA. The mean age was 74 years old with a range from 55 to 89 years. The majority (n = 25, 61%) were baseline American Society of Anaesthesiology (ASA) grade 3–4. Of these 56% underwent EVAR with the remaining 44% repaired open. Mortality rate in those undergoing emergency EVAR was 34.8%, compared with 38.9% in those undergoing open surgery. This difference was not statistically significant. The mean overall length of stay was 13 days. With regard to prognostic indicators of patient outcome, increasing patient age was noted to be significantly associated with increased mortality (p = 0.013), as was increased ASA score at time of surgery (p = 0.029). Conclusions: Mortality rates in those undergoing EVAR for RAAA are comparable with those undergoing open repair. Increasing age and ASA score are significant predictors of mortality in patients with RAAA undergoing intervention.